Identification and characterization of antibacterial peptides produced by Lactobacillus plantarum 1407 - Silpa Sajan; Rupachandra Saravanan (BioImpacts)
Introduction: Peptides from lactic acid bacteria provide health benefits and can inhibit the growth of pathogenic organisms. The present work aimed to isolate and characterize peptides with antibacterial activity from Lactobacillus plantarum 1407. Methods: Peptides were isolated and purified from L. plantarum 1407. The effect of various physiological parameters on the antibacterial activity of the isolated peptides was analyzed. The mode of action of the peptides on indicator organisms was observed using transmission microscopy analysis and flow cytometry analysis . Results: Antibacterial activity and mode of action of peptides isolated from L. plantarum 1407 against gram-positive and gram-negative bacteria have been studied. L. plantarum culture exhibited maximum antibacterial activity at 40 °C, pH 8, and 0.7% salt concentration. The cell-free supernatant (CFS) was concentrated using a 3 kDa ultrafiltration membrane and the peptide fractions (<3 kDa) were further fractionated using Sephadex G-25 gel filtration chromatography. The antibacterial activity of the eluted fractions (F1 to F4) was evaluated using flow cytometry and transmission electron microscopy. F3 fraction exhibited increased antibacterial activity than F1, F2, and F4 fractions against the indicator organisms. Cell membrane damage and leakage of cytoplasmic content of the bacterial cells treated with the antibacterial F3 fraction peptides were observed. Conclusion: The active peptides from L. plantarum 1407 can be potentially used for the treatment of bacterial infections.